ENHANCE OF FLAVOR AND SOME MICROBIAL PHYSICOCHEMICAL AND SENSORIAL PROPERTIES OF YOGURT BY DRIED CANTALOUPE PULP - Al-Zobaay W. J.M.; Al-Zobaay A.H.H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to enhance the flavor compounds, improve sensorial, microbial and physicochemical characteristics of the yogurt product using dried cantaloupe pulp. This study included the estimation of three flavor compounds in the yogurt product (acetaldehyde, acetone, and ethanol), after seven day of refrigeraed storage at 4°C, a wide difference in the levels of flavor compounds among the treatments have been shown, the values ​​of acetaldehyde were in the following treatments (A) control treatment, (H) cantaloupe 1 %, (K) cantaloupe3%, as follows 13.46, 14.27, 24.54 mg/L respectively. Acetone values were 8.38, 5.33, 3.47 mg/L respectively. Ethanol were 10.25, 7.12, 4.29 mg/L respectively. Lactobacillus delbrueckii subsp. Bulgaricus log vaible count after the first day of manufacture were 7.38, 8.53, 8.77 cfu ml-1 for A, H and K treatment respectively, gradually decreased through refrigerated storage to reach after 28 days 6.25, 7.41, 7.60 cfu ml-1 respectively. The log vaible count Streptococcus silvarius subsp. Thermophilus at first day of manufacture were 8.20, 9.66, 9.71 cfu ml-1 for A, H and k treatment respectively, gradually decreased under refrigerated storage to 7.25, 8.50, 8.30 cfu ml-1 respectively after 28 days. Chemical composition did not change, and there were no significant differences among the treatments. Sensory evaluation values showed differences in treatment, the flavor scores for treatments after 28 days of refrigerated storage were (37, 42, 43), the texture were (25, 28, 29), the appearance were (10,14, 14), color (9, 8, 8) for A, H and k treatment respectively. The treatment K was superior as compared to the other treatments with a score of acceptance (94), compared with the control treatment whose score of acceptance was(81) out to 100